Structure-Based Bioisosterism Design, Synthesis, Biological Activity and Toxicity of 1,2,4-Oxadiazole Substituted Benzamides Analogues Containing Pyrazole Rings - Tu, Min-Ting; Shao, Ying-Ying; Yang, Sen; Sun, Bin-Long; Wang, Ying-Ying; Tan, Cheng-Xia; Wang, Xue-Dong (Molecules (Basel, Switzerland), 2022)
In order to discover pesticidal lead compounds with high activity and low toxicity, a series of novel benzamides substituted with pyrazole-linked 1,2,4-oxadiazole were designed via bioisosterism. The chemical structures of the target compounds were confirmed via 1H NMR, 13C NMR and HRMS analysis. The preliminary bioassay showed that most compounds exhibited good lethal activities against Mythimna separate, Helicoverpa armigera, Ostrinia nubilalis and Spodoptera frugiperda at 500 mg/L. Particularly in the case of Mythimna separate, compound 14q (70%) exhibited obvious insecticidal activity. In addition, compound 14h demonstrated good fungicidal activity against Pyricularia oryae with an inhibition rate of 77.8%, and compounds 14e, 14k, 14n and 14r also showed certain antifungal activities (55.6–66.7%). The zebrafish toxicity test showed that the LC50 of compound 14h was 14.01 mg/L, which indicated that it may be used as a potential leading compound for further structural optimization.